PENGEMBANGAN PEMBELAJARAN PAI DENGAN PENDEKATAN SOCIAL EMOTIONAL LEARNING (SEL) - Akif Khilmiyah (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2013)
This paper aims to assess the superiority of Islamic education learning model (PAI) with approach to Social and Emotional Learning (SEL) to strengthen efforts to establish the character and moral values of primary school students. Analysis of inductive method is conducted by an in-depth literature review to discover the design of PAI learning model PAI with approach SEL to shaping the character and moral values of primary school students. Conclusion of this paper shows that model of Social-Emotional Learning (SEL) for PAI should be done in a holistic manner to foster emotional and social intelligence. Holistic learning occurs when PAI curriculum to show themes that encourage the exploration of the authentic and natural events. Through the theme of authentic or natural events that will occur meaningful learning processes and materials that are designed to be interconnected with various areas of curriculum development in the PAI. Holistic learning approach based on inquiry, in which children are involved in planning, explore and share ideas. Education has a meaning that characterize higher moral education, because not only teach what is right and what is wrong, but to inculcate the habit (habituation) about good things, so that students become ideology (cognitive domain) about what is good and wrong , able to feel (affective domain) good value and want to do (psychomotor domain). Moral dimensions of at least include willingness, conscience, value, attitudes, and moral behavior.